Pemalsuan Tanda Tangan Kredit Bank Dalam Pengikatan Hak Jaminan Atas Kebendaan Milik Orang Lain - Syesil Ramaliza Husna; Taupiqqurrahman Taupiqqurrahman (Widya Yuridika, 2023)
Civil law is one of the many positive laws that are actively enforced in Indonesia, which is a constitutional state governed by a wide variety of positive laws. What is more often referred to as "private law" is more accurately described as "civil law," which is a body of legislation that controls many sorts of laws linked to individual interests. In civil law, we often encounter phrases linked to deeds that are illegal (PMH). The very definition of an illegal conduct is one that goes against the law and results in negative consequences for other people. The forgery of bank credit signatures, in which there is a guarantee right for material that belongs to another person and which results in losses for the party that is involved, namely the owner of the property rights to the item, is one of the things that are connected to this illegal crime. When it comes to researching and producing this essay, a qualitative legal research technique was used alongside a statutory approach and a case approach. According to the findings of this research, creditors and borrowers have both participated in illegal behavior. The purpose of this writing is to find out the legal repercussions that are associated with bank credit that was obtained from the act of forging a signature in which there is a guarantee of material that belongs to another person. This credit can be said to be invalid because it does not meet the legal requirements of an agreement, and the debtor is obligated to make up for any losses that were sustained, in addition to being responsible for returning collateral that does not belong to the debtor.